Vascularized Bipedicled Pericranial Flaps for Reconstruction of Chronic Scalp Ulcer Occurring after Cranioplasty - Seok Ho Yoon; Jin Sik Burm; Won Yong Yang; Sang Yoon Kang (Archives of Plastic Surgery, 2013)
BackgroundIntractable chronic scalp ulcers with cranial bone exposure can occur along the incision after cranioplasty, posing challenges for clinicians. They occur as a result of severe scarring, poor blood circulation of the scalp, and focal osteomyelitis. We successfully repaired these scalp ulcers using a vascularized bipedicled pericranial flap after complete debridement.MethodsSix patients who underwent cranioplasty had chronic ulcers where the cranial bone, with or without the metal plate, was exposed along the incision line. After completely excising the ulcer and the adjacent scar tissue, subgaleal dissection was performed. We removed the osteomyelitic calvarial bone, the exposed metal plate, and granulation tissue. A bipedicled pericranial flap was elevated to cover the defect between the bone graft or prosthesis and the normal cranial bone. It was transposed to the defect site and fixed using an absorbable suture. Scalp flaps were bilaterally advanced after relaxation incisions on the galea, and were closed without tension.ResultsAll the surgical wounds were completely healed with an improved aesthetic outcome, and there were no notable complications during a mean follow-up period of seven months.ConclusionsA bipedicled pericranial flap is vascularized, prompting wound healing without donor site morbidity. This may be an effective modality for treating chronic scalp ulcer accompanied by the exposure of the cranial bone after cranioplasty.